1981
DOI: 10.1001/archderm.117.2.86
|View full text |Cite
|
Sign up to set email alerts
|

Nevus comedonicus with epidermolytic hyperkeratosis. A report of four cases

Abstract: Four patients with nevus comedonicus (NC) and the histological changes of epidermolytic hyperkeratosis (EH) are described. The relationship between NC and other epidermal nevi in which EH may occur is further emphasized by this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

1985
1985
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 0 publications
0
17
0
1
Order By: Relevance
“…These are rare and may present before puberty but more often at and around puberty [37, 38]. The lesions may be typical confluent comedones (fig.…”
Section: Comedonal Typesmentioning
confidence: 99%
“…These are rare and may present before puberty but more often at and around puberty [37, 38]. The lesions may be typical confluent comedones (fig.…”
Section: Comedonal Typesmentioning
confidence: 99%
“…These are rare and may present before puberty but more often at and around puberty 37,38 . The lesions may be typical confluent comedones or whiteheads, usually occurring asymmetrically.…”
Section: Comedonal Typesmentioning
confidence: 99%
“…Occurrence of EH in other dermatoses Bullous ichthyosiform erythroderma [7,8] Nevus unius lateris [9,10] Ichthyosis hystrix [10] Keratoderma palmariset plantaris [11] Solitary epidermolytic acanthoma [12] Disseminated epidermolytic acanthoma [13,14] Epidermolytic leukoplakia [15,16] Acrosyringial epidermolytic papulosis neviformis [17] I ncidental finding in a variety acquired solitary skin le sions [18,19] but also in the sebaceous ducts, and was as sociated with dyskeratotic cells and corps ronds in some specimens. Barsky et al [4] reported this variety of nevus comedonicus in 4 patients, 1 of whom had been previously described by Montgomery [20]. In 2 of these cases, the lesions had a linear distribution, in the other 2 they were extensive.…”
Section: Discussionmentioning
confidence: 92%